Ultrasound versus Intravenous Urography in the Evaluation of Patients with Hematuria - Mowafak M. Nakshaband, (Iraqi National Journal of Nursing Specialties, 2023)
Objective: The aim was to compare transabdominal ultrasound examination and intravenous pyelography in theevaluation of patients with hematuria.Methodology: A prospective study of sixty five patients with micro or macroscopical hematuria who were nonrandomly selected at the urosurgical outpatient c-1inic at Azadi General Teaching Hospital a)uhok) duringperiod from January 2006. tQ November 2007. They wel.e assessed by ultrasound qu/S) & urography (rvu),i, _^^J-I I-. _L|__ __ _,_ if needed by other sophisticated and invasive nieasures or interv`ention to determine the definite cause of_ _ _, --__-70`_r`.I \,` +,I,`-.`.hematuria. The result of u/S & IVU was compared according to the definite diagnosis.Results: Out of 43 patients with microscopical hematuria, 23 patients had an obvious cause for hematuria, andout of22 patients with gross hematuria, 16 patients had a definite disorder, and no cause could be detected in therest 26 cases.Urinary calculi were found in 22 patients, 17 of them detected by U/S and 14 patients were detected by IVU. Allbenign (Benign prostatic hypertrophy BPH) or malignant urological tumors (renal and bladder) were diagnosedby U/S but only 4 of them were detected by IVU. Similarly U/S was diagnostic in all urological infections (5patients), while none of them `i/as helpful in diagnosing causes in the urethra like stricture or causes withoutanatomical changes.Conclusions: Sixty five patients with micro or macroscopical hematuria were assessed by ultrasound (U/S) &urography (IVU), to determine the definite cause of hematui.ia. Out of 43 patients with microscopical hematuria,23 patients had an obvious cause for hemafuria, and out of 22 patients with gross hematuria, 16 patients had adefinite disorder, and no cause could be detected in the rest 26 cases.Recommendations: Our results are in favor of using U/S in the initial evaluation of hematuria. However wemustchooseourdiagnostictoolaccordingtothepatient'sconditionandsuspecteddisordercausinghematuria.